Quantitative Techniques : Theory and Problems - Tulsian (P C); Pandey (Vishal) (2004)
Mathematical Statistics
33327a.jpg;33327b.jpg;33327c.jpg;33327d.jpg;33327e.jpg;33327f.jpg
22.5
Keywords: Mathematical Statistics